Decomposition and detoxification of aflatoxin B1 by lactic acid. (14th July 2015) - Aiko, Visenuo; Edamana, Prasad; Mehta, Alka
Abstract: BACKGROUND: A degradation study of aflatoxin B1 (AFB1 ) was carried out using a combination of physical and chemical methods. AFB1 was heated at 80 °C in the presence of acetic, citric and lactic acids for various time periods. The cytotoxicity of the degraded AFB1 and its products were determined by MTT assay. RESULTS: The results showed that among the three organic acids lactic acid was most efficient in degrading AFB1 . Although complete degradation was not observed, up to 85% degradation of AFB1 was obtained when heated for 120 min. Degradation of AFB1 was confirmed by the reduced toxicity on HeLa cells using MTT assay. Treatment with lactic acid resulted in the conversion of AFB1 into two degradation products. These products were observed at lower retention factors of 0.63 and 0.38, which were identified as AFB2 and AFB2a, respectively. The cytotoxicity of AFB2a exhibited much reduced toxicity on HeLa cells compared to that of AFB1 . CONCLUSION: The results have shown the efficiency of lactic acid in degrading AFB1 . This study suggest that lactic acid may be considered for use in the food and feed industry since it is present naturally in food and is considered safe. © 2015 Society of Chemical Industry